Effect of UV Irradiation and Temperature on Free Radical Properties in Dehydrocholic and Ursodeoxycholic Acids: An EPR Study - Małgorzata Dołowy; Paweł Ramos; Barbara Pilawa (International Journal of Photoenergy)
The effect of UV irradiation and temperature on the formation and properties of free radicals in two pharmaceutical important bile acids, such as dehydrocholic (DH) and ursodeoxycholic acids (UDC), was examined. Electron paramagnetic resonance (EPR) spectroscopy was applied to determine the paramagnetic character of UV irradiated and thermally sterilized drugs. Thermal and UV irradiation sterilizations of both compounds were carried out at different conditions according to pharmaceutical norms. The performed EPR measurements of UV irradiated and thermally sterilized DH and UDC samples proved the existence of the complex free radical systems in examined bile acids. Significant influence of UV irradiation in comparison with applied thermal sterilization on free radical concentrations in DH and UDC samples was observed. The results pointed out that thermal method is most suitable for bile acid sterilization. Therefore, this kind of sterilization should be applied in practice.